Use of Information Systems in Company Organizations - Nur baeti; Jelita Ayu Melani (Journal of Information Systems and Management (JISMA), 2023)
The purpose of this study is to determine the use of information systems in an organization, which is widely used by a company. In this study, a descriptive qualitative method was used by reviewing scientific articles taken from Google Scholar by taking notes. From the results of this study, it is known that with an information system, the movement of information owned by a company can be handled and can be arranged systematically so that there is no chaos. The information system is a means of transforming company data which is closely related to the efficiency of the company in its operational activities. Along with the development of technology, the application of information technology in the organization of a company is an important factor to increase the value and competitiveness of the company. So far, there are still many companies that have not implemented information systems as expected because there are no standards for monitoring the use of information technology within the company. While the information system is an important part of managing and carrying out all activities in meeting the company's needs to handle various kinds of problems such as transaction processing and report generation